OPTIMIZATION OF SINGLE CELL PROTEIN PRODUCTION FROM BANANA FRUIT JUICE USING PALMYRAH TODDY MIX UNDER LIQUID FERMENTATION SYSTEM - Sarathadevi, R.; Vasantharuba, S.; Kapilan, R. (My University, 2017)
Introduction: The protein deficiency due to supply of low quality food protein has enhanced the need of new sources of protein rich food. The study was aimed to produce Single Cell Protein (SCP) from banana fruit juice using Palmyrah toddy as a mixed culture under Liquid State Fermentation (LSF) system and to optimize the production conditions to increase the yield. Materials and methods: The LSF experiments were performed in a shaking incubator at 100 rpm. Fermentation media used was composed of Glucose 10g/L, MgSO4 0.5g/L, NaCl 0.1g/L, CaCl2 0.1g/L and KH2PO4 1g/L. It was inoculated with 5 mL of palmyrah toddy (an alcoholic beverage created from natural yeast fermentation of palmyrah inflorescence sap) and the glucose of the fermentation medium was replaced with 10 g/L of banana fruit juice & this is called as banana medium. Initially crude protein was determined to dry microbial cells from banana juice as a sole medium inoculated with toddy according to the Kjeldahl method. Conditions for fermentation were optimized one after another. Initially time at which higher SCP produced was optimized. Next different temperatures were used for fermentation & SCP yield was determined at 72h. Then different concentrations of banana juice were used for fermentation with the already optimized conditions (72h & 30oC). All these selected conditions were applied with different nitrogen sources such as soybean flour, corn flour, ground nut flour ammonium sulphate and peptone added in the fermentation media in order to further optimize the fermentation media. Reduction of nucleic acid from microbial cells using 1N NaOH was carried out in order to increase SCP production as well as reduction of adverse health impacts. All experiments were carried out in triplicates. Statistical analysis was done by Completely Randomized Design (CRD) method using the SAS-8 statistical package. The means of results were compared using Duncan’s Multiple Range Test (DMRT at 0.05α) Results: before optimization crude protein yield was 34.02% for banana fruit juice as a sole medium. Banana fruit juice medium showed optimum SCP production at 72 hours of fermentation, 30oC temperature and 5% of fruit juice concentration and the maximum crude protein yielded for banana medium was 38.8% before the addition of inorganic nutrient supplements (banana juice as a sole medium). When medium was supplemented with inorganic nutrients (KH2PO4, MgSO4.7H2O, CaCl2, and NaCl) except nitrogen source the crude protein yield was increased to 41.18% from 38.8% (p<0.05). After the reduction of nucleic acid content of SCP, crude protein yield increased further by 0.85% (42.03%) for banana medium. When organic and inorganic nitrogen sources were added with available nitrogen sources such as soybean flour, corn flour, ground nut flour ammonium sulphate and peptone, the highest crude protein was obtained with soybean flour (40.88%) and the lowest was with corn flour (31.55%). There was no significant (p>0.05) increase in the amount of crude protein, when medium was supplemented with nitrogen source. Discussion: SCP production was significantly increased after optimization of conditions (fermentation time, temperature and banana fruit juice concentration) and reduction of nucleic acid from microbial cells. Conclusion: It could be concluded that effective single cell protein could be possible from inexpensive banana fruit juice with natural palmyrah toddy mixed culture under optimized condition. Large scale studies and quality analysis should be done with a bioreactor system before recommending this for industrial application
Keywords: Banana fruit juice; fermentation; optimization; Single Cell Protein (SCP)